1991
DOI: 10.1037/0012-1649.27.4.587
|View full text |Cite
|
Sign up to set email alerts
|

Primary appraisal of the Strange Situation: A cross-cultural analysis of preseparation episodes.

Abstract: Studies in various countries-among them Germany, Holland, Israel, Japan, Sweden, and the United States-have reported Strange Situation distributions that differ markedly across and within cultures, thus raising doubts as to whether infant behavior in the Strange Situation can be regarded as a valid index of the security of attachment, at least in a cross-cultural context. It is proposed here that a fuller understanding of infant behavior in the Strange Situation requires an assessment of what Connell and Golds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…For example, in a series of studies conducted by Sagi and his colleagues, it was demonstrated that the vast majority of insecure infants in Israel are ambivalent (Sagi et al, 1985(Sagi et al, , 1994. This poses a question about whether the meaning of ambivalent attachment in Israel is similar to ambivalence in other cultures (Sagi, van IJzendoorn, & Koren-Karie, 1991). The findings of the present study support the contention that cultural context may be a relevant (moderating) factor of the child's attachment.…”
Section: Discussionsupporting
confidence: 85%
“…For example, in a series of studies conducted by Sagi and his colleagues, it was demonstrated that the vast majority of insecure infants in Israel are ambivalent (Sagi et al, 1985(Sagi et al, , 1994. This poses a question about whether the meaning of ambivalent attachment in Israel is similar to ambivalence in other cultures (Sagi, van IJzendoorn, & Koren-Karie, 1991). The findings of the present study support the contention that cultural context may be a relevant (moderating) factor of the child's attachment.…”
Section: Discussionsupporting
confidence: 85%
“…This possibility seems to be unlikely in ligbt of previous data (Sagi et al, 1985) showing that Strange Situation classifications were unaffected by timing of assessment. Finally, recent meta-analyses demonstrate that, after years of debate regarding the validity of the Strange Situation in a cross-cultural context, use of the procedure in various cultural contexts can be considered cross-culturally valid (Sagi, 1990;Sagi, van IJzendoorn, & Koren-Karie, 1991;van IJzendoorn, 1990;van IJzendoorn & Kroonenberg, 1988).…”
Section: Sagi Et Al 1001mentioning
confidence: 99%
“…But the SS may not be psychologically equivalent for all infants, because infants differ in how familiar they are with the components of the SS procedure as a result of variation in daily caregiving routines, and this may affect how stressful they find it. Most commonly this issue has been raised in discussing the differences in attachment behavior and the distribution of attachment types observed in different cultures (Grossmann, Grossmann, Spangler, Suess, & Unzner, 1985;Lamb, Thompson, Garner, & Charnov, 1985, 1986Miyake, Chen, & Campos, 1985;Sagi, Lamb, Lewkowicz, Shoham, Dvir, & Estes, 1985;Sagi, van IJzendoorn, & Koren-Karie, 1991;van IJzendoorn & Kroonenberg, 1988;Zach & Keller, 1999). In countries around the world, the rate of avoidant attachment (Type A) has been observed to range from 0% (in Japan) to 49% (in Germany); the rate of resistant attachment (Type C), to range from 4% (in Sweden and Holland) to 66% (in Israeli kibbutzim) (Sagi et al, 1991).…”
Section: Limitations Of the Strange Situation Assessment Of Attachmentmentioning
confidence: 99%
“…Most commonly this issue has been raised in discussing the differences in attachment behavior and the distribution of attachment types observed in different cultures (Grossmann, Grossmann, Spangler, Suess, & Unzner, 1985;Lamb, Thompson, Garner, & Charnov, 1985, 1986Miyake, Chen, & Campos, 1985;Sagi, Lamb, Lewkowicz, Shoham, Dvir, & Estes, 1985;Sagi, van IJzendoorn, & Koren-Karie, 1991;van IJzendoorn & Kroonenberg, 1988;Zach & Keller, 1999). In countries around the world, the rate of avoidant attachment (Type A) has been observed to range from 0% (in Japan) to 49% (in Germany); the rate of resistant attachment (Type C), to range from 4% (in Sweden and Holland) to 66% (in Israeli kibbutzim) (Sagi et al, 1991). In general, the distribution of attachment types is tilted toward greater avoidance in Western Europe and greater resistance in Eastern nations (Sagi, van IJzendoorn, Scharf, Joels, Koren-Karie, Mayseless, & Aviezer, 1997;van IJzendoorn & Kroonenberg, 1988).…”
Section: Limitations Of the Strange Situation Assessment Of Attachmentmentioning
confidence: 99%
See 1 more Smart Citation